Pengaruh Motivasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Pos Indonesia (Persero) Cabang Ciputat Kota Tangerang Selatan - Muhamad Ali Solehudin; Yan Kristian Halomoan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This quantitative research aims to analyze and prove the influence of Motivation (X1) and Physical Work Environment (X2) variables on Employee Performance (Y) at PT Pos Indonesia (Persero) Ciputat Branch, South Tangerang City, using a sample of 87 respondents with a linear regression equation Y = 20.962 + 0.224 X1 + 0.250 X2. Partially, Motivation (X1) is proven to have a positive and significant effect on Performance (Y), indicated by the t-value (3.483) > t-table (1.988) and a significance value of 0.001 < 0.05. Therefore, H0 is rejected and Ha1 is accepted, with a partial contribution of 12.5%. Similarly, the Physical Work Environment (X2) also has a positive and significant effect, as evidenced by the calculated t value (3.347) > t table (1.988) and a significance of 0.001 < 0.05, so that H0 is rejected and Ha2 is accepted, with a partial contribution of 11.6%. Simultaneously, both variables have a significant effect on Employee Performance, as indicated by the calculated F value (9.893) > F table 3.11 and a significance of 0.000 < 0.05, so that H0 is rejected and Ha3 is accepted. The simultaneous determination coefficient (R²) is 0.191 or 19.1%, while the remaining 80.9% is influenced by other factors outside the model. The conclusion of this study confirms that Motivation and Physical Work Environment, both individually and together, have a strong positive and significant effect in improving Employee Performance at PT Pos Indonesia (Persero) Ciputat Branch, South Tangerang City. Keywords: motivation, physical work environment, employee performance.